Impact of electronic AKI alert/care bundle on AKI inpatient outcomes: a retrospective single-center cohort study - Michael Chen-Xu; Christopher Kassam; Emma Cameron; Szymon Ryba; Vivian Yiu (Renal Failure)
Background Outcomes among acute kidney injury (AKI) patients are poor in United Kingdom (UK) hospitals, and electronic alerts and care bundles may improve them. We implemented such a system at West Suffolk Hospital (WSH) called the ‘AKI order set’. We aimed to assess its impact on all-cause mortality, length of stay (LOS) and renal function among AKI patients, and its utilization.Methods Retrospective, single-center cohort study of patients ≥ 18 years old with AKI at WSH, a 430-bed general hospital serving a rural UK population of approximately 280,000. 7243 unique AKI events representing 5728 patients with full data were identified automatically from our electronic health record (EHR) between 02 September 2018 and 1 July 2021 (median age 78 years, 51% male). All-cause mortality, LOS and improvement in AKI stage, demographic and comorbidity data, medications and AKI order set use were automatically collected from the EHR.Results The AKI order set was used in 9.8% of AKI events and was associated with 28% lower odds of all-cause mortality (multivariable odds ratio [OR] 0.72, 95% confidence interval [CI] 0.57–0.91). Median LOS was longer when the AKI order set was utilized than when not (11.8 versus 8.8 days, p < .001), but was independently associated with improvement in the AKI stage (28.9% versus 8.7%, p < .001; univariable OR 4.25, 95% CI 3.53–5.10, multivariable OR 4.27, 95% CI 3.54–5.14).Conclusions AKI order set use led to improvements in all-cause mortality and renal function, but longer LOS, among AKI patients at WSH.